Estudo da gestão da comunicação da Universidade Federal de Santa Maria a partir de sua presença na mídia local - Hartmann, Laura Beatriz (2018)
This research aimed to answer the following question: "How was the communication management in the Federal University of Santa Maria (UFSM), headquartered in Santa Maria, according to what was published by the local media outlets during the year of 2016?". Therefore, the purpose of the study was to investigate the communication management in the Federal University of Santa Maria through local vehicles of mass communication. Consequently, the theoretical framework used in this research was built upon the following concepts: institutional image (Brandão), communication and public interest (Faria), and citizenship (Kocourek). The methodology was based on two specific research tools, i.e., image audit (Duarte) and content analysis (Bardin). The main results are summarized as follows: the communication management in the Federal University of Santa Maria during that period of time was neutral, characterized by institutional themes, greater diffusion of the newspaper “Diário de Santa Maria” as well as little use of material made available by the University. These results suggest the need of content adaptation for the press, restructuring of the UFSM tool in the Media, and offer of unique news scripts.